Hope and Fear in Stephen King's "The Mist" (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
Hope and Fear are something that lies in the deep of the human mind that affect how people act. This research is conducted to reveal fear and hope in society as part of human psyche that build its very foundation. The topic of this research is hope and fear in Stephen King’s The Mist. The research instrument uses observation sheets, while the data collection is based on the library research. This is a descriptive qualitative research that used structuralism theory by Levi-Strauss. By using the structuralism theory, the analysis of the study was conducted through binary opposition found in the novel. This research results in several findings as follows: 1) People lose themselves as human when fear constantly breaks them, while hope is the one that can keep them as human even in the hard times. 2) In religion aspect, fear has changed the way people think about God. The disaster, the death, and the monster are said to be God’s will. It shows that the fundamental of belief is changed from blessing life to cursing life. Furthermore, society’s moral has degenerated that they justify the wrong thing as right, and otherwise because they only think about their safety. Keywords: Binary Opposition, Fear, Hope, Society, Structuralism